The Impact of Gut Microbiome on Metabolic Disorders During Catch-Up Growth in Small-for-Gestational-Age - An, Jingjing; Wang, Junqi; Guo, Li; Xiao, Yuan; Lu, Wenli; Li, Lin; Chen, Lifen; Wang, Xinqiong; Dong, Zhiya (Frontiers in Endocrinology, 2021)
Objective: Catch-up growth (CUG) in small for gestational age (SGA) leads to increased risk of metabolic syndrome and cardiovascular diseases in adults. It remains unclear if microbiota could play an important role in CUG-SGA independent of genetic or nutritional factors. The present study explored the role of gut microbiota in, and its association with, metabolic disorder during CUG-SGA. Methods: An SGA rat model was established by restricting food intake during pregnancy, and the rats were divided into catch-up growth (CUG-SGA) and non-catch-up growth (NCUG-SGA) groups based on body weight and height at the fourth postnatal week. High-throughput sequencing of 16S rRNA was conducted to detect the diversity and composition of the gut microbiota. Fecal short-chain fatty acids (SCFAs) were detected by gas chromatography-mass spectrometry. Transcriptome sequencing of liver tissue was performed and verified using real-time PCR. Concentrations of insulin and total cholesterol were determined using enzyme-linked immunosorbent assay, and blood glucose was measured using a blood glucose meter. Results: The composition of gut microbiota in CUG-SGA rats differed from that of NCUG-SGA rats, with reduced abundance of Lactobacillus in the CUG-SGA group. The decrease in Lactobacillus was significantly associated with increased body weight and upregulated insulin and total cholesterol levels. Seven SCFAs were significantly higher in the CUG-SGA group than in the NCUG-SGA group. Additionally, seven SCFAs were positively associated with clinical indices such as weight, body mass index, insulin, and total cholesterol. Transcriptomic data revealed that insulin-like growth factor-2 expression was significantly decreased in CUG-SGA rats and was associated with a decrease in Lactobacillus bacteria. Conclusion: Lactobacillus may regulate SCFAs and thus influence the metabolic disorder during CUG in SGA.